Fabrication and characterisation of RF MEMS capacitive switches tuned for X and Ku bands. (2018) - Shajahan, E.S.; Bhat, M.S.
Microelectromechanical systems (MEMS) capacitive switches discussed in this paper employ electrostatic actuation to perform switching. Capacitive switches employ inductive tuning for excellent switching characteristics in X and Ku bands. Employing inductive tuning is found to increase the switch beam inductance by a few tens of pico-henry. This enhances the Q factor and enables tuning of isolation over a narrow band of frequencies. Beam inductance can be extracted from the simulated isolation characteristics of the switch by curve fitting. This paper presents design, fabrication and characterisation of inductive tuned MEMS capacitive switches tuned for X and Ku bands. The devices are fabricated on high resistive (10 KΩ) silicon substrate by a five mask process. The characterisation of the fabricated devices are conducted using Cascade probe station and high frequency Power network analyser. Characterisation results show an actuation voltage of 18.5 volts. The insertion - loss and isolation are better than 0.5 dB and -40 dB respectively in the 8-18 GHz band.